1988
DOI: 10.1161/01.cir.77.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Marked platelet activation in vivo after intravenous streptokinase in patients with acute myocardial infarction.

Abstract: We assessed thromboxane biosynthesis as an index of platelet activation in 6 patients with acute myocardial infarction receiving intravenous streptokinase. Urinary 2,3-dinor-thromboxane B2 and plasma 1 1-dehydro-thromboxane B2, major enzymatic metabolites of thromboxane A2, were markedly increased after intravenous streptokinase (11,063 ± 2758 pg/mg creatinine and 33 ± 10 pg/ml, respectively) compared with levels in patients not receiving thrombolytic therapy (502 ± 89 pg/mg creatinine and 3 0.7 pg/ml). Prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
105
0
6

Year Published

1990
1990
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(114 citation statements)
references
References 42 publications
3
105
0
6
Order By: Relevance
“…TXA 2 is in large part derived from platelets, and increased TXA 2 formation is a marker of platelet activity. 44,45 Therefore, we saw no evidence that the reduction in PGI 2 enhanced platelet activity in vivo. Indeed, given its expression in proliferating VSMCs, it is possible that the COX-2 activity contributes to the progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 69%
“…TXA 2 is in large part derived from platelets, and increased TXA 2 formation is a marker of platelet activity. 44,45 Therefore, we saw no evidence that the reduction in PGI 2 enhanced platelet activity in vivo. Indeed, given its expression in proliferating VSMCs, it is possible that the COX-2 activity contributes to the progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 69%
“…Given that immunoassays are currently available only for iPF 2␣ -III, 38 this observation is relevant to clinical investigation. This is especially so because COX activation may coincide with oxidant stress in clinical settings such as ischemiareperfusion syndromes 39 and in cigarette smoking. 40 Recently, Davi et al 41 reported that urinary levels of immunoreactive iPF 2␣ -III are elevated in hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to establish the efficacy of aspirin through clinical trials in cardiovascular disease were frustrated for more than a decade because populations were diluted with respect to likely benefit from the drug. 42 The development of methods to estimate thromboxane biosynthesis using urinary metabolites not only aided in the selection of low doses of aspirin for cardiovascular indications 42 but also identified unstable angina 43 and therapeutic thrombolysis 44 as biochemically rational targets for aspirin therapy, a contention borne out by the results of randomized clinical trials. 45,46 Clinical trials of antioxidants have been performed in the past without a clear in vivo biochemical rationale, either for the choice of clinical targets or for the selection of antioxidant doses of such compounds.…”
Section: Discussionmentioning
confidence: 99%
“…4,[30][31][32] The clinically observed thrombi contain numerous platelets, and there is evidence that circulating platelets can be activated in the diseased arterial segment, causing increases in transmyocardial thromboxane concentrations.33-35 When the circulating platelets are activated but not enmeshed in the thrombus, they can form small intramyocardial aggregates, which Davies et a136 have described in patients with unstable angina who experienced sudden ischemic cardiac death. Additionally, there have been recent reports suggesting even greater platelet activation during the infusion of thrombolytic agents, that is, streptokinase and rt-PA. 37,38 Platelet aggregates interacting with a damaged endothelial surface or exposed subendothelial component are a major factor early in coronary artery thrombosis and subsequent rethrombosis. 39 The release of thromboxane and serotonin from the activated platelets is one mechanism proposed as a cause of reocclusion.…”
Section: Discussionmentioning
confidence: 99%